PERBANDINGAN HASIL BELAJAR SISWA ANTARA PEMBELAJARAN MENGGUNAKAN PBL DAN DISCOVERY LEARNING - Puspita Indah Rahayu; Undang Rosidin; Abdurrahman Abdurrahman (Jurnal Pembelajaran Fisika, 2015)
Abstract: Comparison of student learning outcomes between learning using Problem based learning (PBL) and discovery learning on the optical material. This study aimed to determine the difference and increase student learning outcomes on the implementation of PBL and discovery learning on the optical material. The design of this study used in one group pretest-posttest design. In the experimental class the average score of student learning outcomes was 53.90 and the increasing of the average score of student learning outcomes was 28.30 with N-gain 0.37 (medium category). In the control class the average score of student learning outcomes was 38.10 and the increasing of the average score of student learning outcomes was 9.60 with N-gain 0.13 (lower category). The result showed that there were differences in student learning outcome between experimental class that has been applied PBL and control class that has been applied discovery learning. It canbe conclude that the implementation of PBL more effectively to improve student learning outcomes.Abstrak: Perbandingan hasil belajar siswa antara pembelajaran menggunakan problem based learning (PBL) dan discovery learning pada materi optik. Penelitian ini bertujuan untuk mengetahui perbedaan dan peningkatan hasil belajar siswa pada penerapan PBL dan discovery learning pada materi optik. Desain penelitian yang digunakan adalah One Group Pretest-Posttest Design. Pada kelas eksperimen skor rata-rata hasil belajar siswa adalah 53.90 dan kenaikan skor rata-rata hasil belajar siswa sebesar 28,30 dengan N-gain sebesar 0,37 (kategori sedang). Pada kelas kontrol skor rata-rata hasil belajar siswa adalah 38.10 dan kenaikan skor rata-rata hasil belajar siswa sebesar 9,60 dengan N-gain sebesar 0,13 (kategori rendah). Hasil penelitian menunjukkan bahwa terdapat perbedaan hasil belajar siswa antara kelas eksperimen yang menerapkan PBL dan kelas kontrol yang menerapkan discovery learning. Hasil tersebut menunjukkan bahwa penerapan PBL lebih efektif untuk meningkatkan hasil belajar siswa.Kata kunci: discovery learning, hasil belajar, problem based learning